Behavioral inhibition, behavioral activation and impulsivity in the Dark Triad - Nedeljković, Boban; Tucaković, Lana (Psihološka istraživanja, 2023)
Gray’s Reinforcement Sensitivity Theory postulates that the behavioral inhibition system (BIS) is responsible for regulating anxiety and fear in response to external stimuli, while the behavioral activation system (BAS) is responsible for processing positive cues such as rewards. Dickman’s model distinguishes dysfunctional impulsivity (DI), characterized by non-reflective decision-making, from functional impulsivity (FI), which reflects the propensity of making quick decisions when advantageous. The aim of this study was to investigate the potential of BIS/BAS and DI/FI to explain the variance in the Dark Triad traits. The sample included 318 convenient-recruited participants (Mage = 28.67, SDage = 8.95; 75.2% females) who completed BIS/BAS scales (BIS, BAS Fun Seeking, BAS Reward Responsiveness, and BAS Drive), Dickman’s Impulsivity Inventory and Short Dark Triad (Machiavellianism, narcissism, and psychopathy). BAS Reward Responsiveness and BAS Drive were significant predictors of Machiavellianism, which indicated that individuals high in this trait could be sensitive to positive reinforcement. BIS, BAS Fun Seeking, and DI were significant predictors of psychopathy, while BIS, all BAS scales, and FI were significant predictors of narcissism. These results suggested that poor inhibition, low impulse control, and a strong tendency to approach pleasure-oriented activities are the factors that significantly contribute to explaining the surface of psychopathy, and they could be seen as particularly important for maladaptive behavior. On the other hand, individuals with high narcissism may be sensitive to positive reinforcement, goal-oriented, and exhibit functional impulsivity, which allows them to capitalize on opportunities.
Keywords: BIS/BAS; Functional impulsivity; Dysfunctional impulsivity; Dark Triad